Survival and colonization of nematodes in a composting process. Issue 2 (7th May 2013) - Steel, Hanne; Verdoodt, Freija; Čerevková, Andrea; Couvreur, Marjolein; Fonderie, Pamela; Moens, Tom; Bert, Wim
Abstract Nematodes are omnipresent in composts and are active in virtually all stages of the composting process. Major shifts in species composition, life strategies, and feeding behavior occur during the composting process. Due to the heat peak, nematodes can be virtually absent, but several taxa appear immediately when the temperatures drop. These comprise both taxa present before the heat peak and new taxa. However, it is not known how nematodes populate the compost. In this study, we aimed to assess the survival and colonization capacity of nematodes in compost. Our results showed that composting processes inaccessible to insects or not in contact with soil did not significantly influence nematode succession during composting. However, differences between treatments were found for some specific taxa (i.e., for Acrostichus sp., Neodiplogasteridae sp., Nygolaimoides sp., and Rhabditidae sp. 1), illustrating the importance of insects for the dispersal of nematodes to compost. Experiments in the lab with the blue bottle fly as a possible carrier demonstrated actual transport of nematodes isolated from compost by the fly (i.e., Halicephalobus cfr. gingivalis, Diploscapter coronatus, Diplogasteritus sp., Acrostichus sp., and Mesorhabditis sp.). Juveniles and dauer stages of Aphelenchoides sp., Panagrolaimus sp., and rhabditids survived an experimentally induced temperature peak, while members of Tylenchidae did not. In conclusion, our results indicate that the rapidly changing nematode community in compost is the result of both differential survival and colonization capacities.